PENGEMBANGAN FRAMEWORK EVALUASI KINERJA GREEN SUPPLY CHAIN MANAGEMENT MENGGUNAKAN MODEL GSCOR DAN PENDEKATAN AHP - Mawarni, Igga; Yuliawati, Evi (Universitas Putera Batam, 2025)
Automotive industry holds a crucial role within the supply chain, including its impact on the environment. Thus, through the implementation of Green Supply Chain Management (GSCM) became a relevant method to improve result and sustainability. This research aims to evaluate GSCM through developing the Green Supply Chain Operation Reference (Green SCOR) framework based on the Analytical Hierarchy Process (AHP) method. CVT-producing companies are the object of this research. This research began with literature studies, observation, and interview to establish the Key Performance Indicators (KPI), followed with performance evaluation with the Three-level GSOR method through Snorm normalization calculation and AHP weighting method. Results shown indicates final GSCM Score for the CVT manufacturing company to be 134.14, categorized as excellent. Such score indicates a good overall implementation of Green Supply Chain Management. Even so, several KPIs are to be improved, such as Percentage Quality Accuracy by Supplier and Mean Time To Repair (MTTR), while also enhancing the return and market claim aspects